8-Hydroxy-5,7-dimethylquinolin-1-ium hydrogen sulfate - Thanigaimani, Kaliyaperumal (International Union of Crystallography, 2012)
The quinoline ring system of the title salt, C(11)H(12)NO(+)·HSO(4) (−), is essentially planar, with a maximum deviation of 0.054 (2) Å for all non H atoms. In the crystal, the cations and anions are linked via N—H⋯O, O—H⋯O and weak C—H⋯O hydrogen bonds, and are stacked respectively in columns along the a axis. π–π stacking interactions, with centroid–centroid distances of 3.5473 (12) and 3.6926 (12) Å, are also observed. The crystal studied was an inversion twin with refined components of 0.43 (7):0.57 (7).